Implementasi Web-Service untuk Pengembangan Layanan Pariwisata Terpadu - Tri Kuntoro Priyambodo (Teknoin, 2005)
This paper describes an integrated tourism information system developed using web-service technology. In order to give a clear picture of multi-tier system used for developing web-services, two cases (“WisataBudayaJawa web-service” for giving recommendations for users to select tourism objects to visit in the areas of the Province of Central Java and the Province of Yogyakarta; and “Kurs web-service” for delivering information on foreign currency exchange rate) are presented. The results of the study show that web-service enable to simplify operations conducted by a programmer in inputing and gathering outputs. In addition, web-service is operating-systems independent.  Keywords:: web-service, web programming, network, distributed system.